Analyzing influences : research on decision making and the curriculum - Campbell, Mark Robin; Thompson, Linda K. (Advances in music education research., 2015)
Analyzing Influences: Research on Decision Making and the Music Education Curriculum examines influences on research in music teacher preparation, practices, and policies. These influences include administrators' perspectives, preservice music educators' beliefs, and in-service teachers' practices. Invited essays offer insights into past and present trends in music teacher preparation.This collection of studies represents best thinking in the field and serves as an impetus for further research and action. Each author's analysis on the influences affecting their specific areas provides insights into key issues affecting decision making processes. This volume is a significant addition to the libraries of Colleges of Education and Schools of Music, as well as an important reference for music scholars and educators, researchers, and graduate students who are concerned with advancing both the scope and quality of research in the study of music teaching and learning.